Unawareness, Beliefs and Games - Aviad Heifetz; Martin Meier; Burkhard C. Schipper (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
We define a generalized state-space model with interactive unawareness and probabilistic beliefs. Such models are desirable for many potential applications of asymmetric unawareness. We develop Bayesian games with unawareness, define equilibrium, and prove existence. We show how equilibria are extended naturally from lower to higher awareness levels and restricted from higher to lower awareness levels. We use our unawareness belief structure to show that the common prior assumption is too weak to rule out speculative trade in all states. Yet, we prove a generalized ``No-trade'' theorem according to which there can not be common certainty of strict preference to trade. Moreover, we show a generalization of the ``No-agreeing-to-disagree'' theorem.
Keywords: C72; C70; D82; D80; 330; unawareness; awareness; type-space; Bayesian games; incomplete information; equilibrium; common prior; agreement; speculative trade; Erkenntnistheorie; Wahrnehmung; Wissen; Information; Wertpapierspekulation; Theorie